Ghrelin expression in normal kidney tissue and renal carcinomas - Dagli, Adile F.; Aydin, Suleyman; Karaoglu, Aziz; Akpolat, Nusret; Ozercan, Ibrahim H.; Ozercan, Mehmet R. (Elsevier Gmbh, 2009)
Ghrelin expression in cancers is either reduced/absent or increased depending on the organs involved. The aims of this study were to investigate: (i) whether there are differences in ghrelin peptide expression between kidney tissues from a series of renal cell carcinoma cases, oncocytomas, and normal controls; (ii) whether there are correlations between tissue ghrelin levels in a series of renal carcinoma cases and normal controls; and (iii) how normal is kidney ghrelin expression per mg tissue as compared with the normal stomach tissue ghrelin level. We studied 7 normal stomach and 7 normal kidney samples, 21 clear cell renal carcinomas, 7 chromophobe type renal cell carcinomas (RCC), 7 papillary type RCC, and 7 oncocytoma samples. Tissue ghrelin expression was measured by RIA and immunohistochemistry. Grades 1-3 clear renal cell carcinomas, chromophobe type RCC, papillary type RCC. and oncocytomas expressed 88%, 94%, 95%, 51%, 75%, and 48% less ghrelin than the normal kidney, respectively. Overall, we concluded that ghrelin expression in renal cell carcinoma tissues is always lower than that in normal kidney or is absent. This low level or lack of ghrelin may play a role in the etiopathogenesis and progression of cancer. (C) 2008 Elsevier GmbH. All rights reserved.
Keywords: Ghrelin; Renal cell carcinoma; Oncocytoma